Nurali Kabul and the artistic expression of imagery in his short stories (“The Patient” and “The Trial”) - A. M. Talipova (Journal of Indigenous Culture, Tourism, and Language, 2025)
Purpose: This study examines the distinctive features of artistic imagery in the short stories of Nurali Kabul, focusing on their aesthetic and ideological dimensions. Method: The analysis is grounded in theoretical perspectives from Sidney, Belinsky, Potebnya, Fitrat, Warren, Djurishin, Dima, Timofeev, Pospelov, Eagleton, and other scholars who contributed to artistic image theory. Results: Findings reveal a complex system of imagery characterized by psychological depth, emotional nuance, and structural significance within Kabul’s artistic thought. The harmony of national and universal values, along with lyricism, simplicity, and psychological richness, emerges as central traits of his poetics. Conclusion: Kabul’s short stories reflect a unique artistic style that synthesizes national cultural identity with contemporary aesthetic sensibilities. Limitation: The study is limited to textual analysis of short stories and does not incorporate comparative or empirical reader-response data. Contribution: This research enriches literary criticism on modern Uzbek prose by offering a comprehensive aesthetic and ideological interpretation of Kabul’s imagery.